Community Empowerment Program Model For MSMEs’ Actors Affected by Covid-19 in Special Region of Yogyakarta - Nur Faidati; Muhammad Khozin; Gerry Katon Mahendra (Universitas Muhammadiyah Yogyakarta, 2021)
This study focuses on modeling community empowerment programs for MSMEs affected by Covid-19 in DIY. Pandemic Covid-19 that has occurred since the end of 2019 has impacted the cessation of activity of MSMEs in DIY. The absence of activity in the tourist area, the implementation of online learn- ing has a slight influence on this condition. The research method used in this research is the descriptive exploratory qualitative research method. The purpose of this research is to determine the appropriate empowerment model for MSMEs during the Covid-19 pandemic and to contribute in the form of an academic policy paper for relevant stakeholders. This study uses a desk study and interview technique. Desk studies are carried out through secondary data tracking. Interviews were conducted with regional apparatus organizations (OPD) which handle MSMEs and MSMEs’ actors. From the research conducted, it is known that the efforts made by the Provincial / Regency / City Governments within the scope of DIY or CSO in order to help MSMEs actors to survive in this pandemic situation if they are framed by using the empowerment models are used the second and third models. The second model seeks to strengthen the potential or power possessed by the community by implementing concrete steps, accommodating various inputs, providing good infrastructure and facilities. The third model seeks to empower the community in the sense of protecting and defending the interests of the weak community. From the research, it concludes that the model of empowering MSMEs affected by Covid-19 in DIY, both carried out by the local government and by CSO such as Muhammadiyah / ‘Aisyiyah is done to strengthen the potential or power possessed by MSMEs by implementing real steps, accommodating various inputs, providing infrastructure and facilities good and empowering the community in the sense of protecting and defending the interests of MSMEs.